Screening of sugar alcohols and their binary eutectic mixtures as phase change materials for low-to-medium temperature thermal energy storage. (Ⅲ): Thermal endurance. (15th October 2020) - Shao, Xue-Feng; Yang, Sheng; Wang, Chao; Wang, Wu-Jun; Zeng, Yi; Fan, Li-Wu
Abstract: The thermal endurance of four pure and three binary eutectic mixture sugar alcohols were examined as a complementary work to the previous screening efforts based on the phase change behaviors towards latent heat storage. It was shown that both the melting point and latent heat of fusion of these sugar alcohols degrade with increasing the heating duration, and that a higher degree of superheat leads to faster degradation. The melting point drift mainly attributes to the shrinking range of hydrogen bonding, whereas the decay of latent heat is likely resulted from the disruption of hydrogen bond networks and incomplete crystallization. Among the various candidates, erythritol exhibits the best thermal endurance. The infrared spectra demonstrated that sugar alcohols can be oxidized to generate aldehydes upon heating when exposed to air. It was also found that the duration for 10% degradation of the latent heat of fusion of inositol can be extended by ∼9 times when being protected by nitrogen gas. However, although the introduction of nitrogen gas could efficiently improve the thermal endurance, other complex reactions can still occur in inert gas atmosphere at high temperatures, leaving the room for further improving the thermal endurance of sugar alcohols toward real-world applications. Highlights: Thermal endurance performance was tested for select pure and mixture sugar alcohols. Degradation behaviors were analyzed using the constant-temperature kinetics model. Melting point and latent heat of fusion tend to degrade along with heating duration. Candidates exposed to air suffer from oxidation and generate aldehydes materials. Inert gas protection is helpful to improve the thermal endurance of sugar alcohols.